MicroRNA-155 acts as a diagnostic and prognostic biomarker for oesophageal squamous cell carcinoma. Issue 1 (1st January 2020) - Zheng, Ying-Juan; Liang, Tian-Song; Wang, Juan; Zhao, Jing-Yi; Zhai, Su-Nan; Yang, Dao-Ke; Wang, Li-Dong
Abstract: MicroRNA-155 is over-expressed in many human cancers, but researches on its association with malignant oesophageal squamous cell carcinoma (ESCC) are limited. The aim of the present study was to evaluate the potential value of miR-155 as a biomarker for ESCC diagnosis and prognosis. In this study, we found that miR-155 was significantly increased in ESCC tissues compared with the paired adjacent tissues and healthy normal controls ( p < .001), according to qRT-PCR, which suggested that miR-155 might act as an oncogene in ESCC. In addition, clinical features such as the depth of tumour invasion, tumour size, and TNM stage were all proved to impact the expression of miR-155 ( p < .01). Then, ROC curve analysis, reaching an AUC of 0.870, and a sensitivity and specificity of 83.5% and 77.5%, respectively, revealed that miR-155 was a predictive factor for ESCC. As well, high expression of miR-155 was associated with poor overall survival of the patients (log-rank test, p = .004), according to Kaplan-Meier analysis. MiR-155 might be an independent predictor for overall survival in ESCC patients, manifested by Cox regression analysis (HR = 16.94, 95%CI = 3.33–86.12, p = .001). Taken together, miR-155 could be an independent diagnostic and prognostic biomarker for ESCC.